Social Networking Sites Addiction and Materialism Among Chinese Adolescents: A Moderated Mediation Model Involving Depression and Need to Belong - Wang, Pengcheng; Lei, Li; Yu, Guoliang; Li, Biao (Frontiers in Psychology, 2020)
Recent research indicates that social networking site (SNS) addiction is positively associated with materialism. However, little attention has been paid to the potential mechanisms in this relationship. This study tested the mediating role of depression and the moderating role of need to belong (NTB) in the relationships between SNS addiction and adolescents’ materialism. This research model was tested among 733 adolescents in China (mean age = 16.79 years, SD = .91). The findings indicated that both SNS addiction and NTB were positively related to adolescents’ materialism. Mediation analyses showed that depression mediated the association between SNS addiction and adolescents’ materialism. Moderated mediation indicated that the effect of SNS addiction on materialism and the effect of SNS addiction on depression were exacerbated by NTB. This study can advance our understanding of how SNS could contribute to adolescents’ materialism in this digital society.